Risk Factors Associated with Delivering Low Birth Weight Infants in Term Pregnant Women in Pathum Thani Hospital - Nopanitaya, Tippawan (Journal of Health Science of Thailand, 2018)
Low birth weight infants could have several associated factors. The objective of this study was to determine risk factors associated with term pregnant women who delivered infants with birth weight less than 2500 grams in Pathum Thani Hospital. The samples were 910 singleton pregnant women with gestational age 37 completed weeks or more that delivered newborns during 1st October 2006 - 30th September 2007. Risk factors were investigated in the group of 182 cases that delivered low birth weight infants which weighted less than 2500 grams in comparison to the control group of 728 cases that delivered normal weight infants of 2500 grams or more. The results revealed that risk factors that are significantly related to low birth weight infants were young mothers aged less than 20 years (Odd ratio 1.60, 95% CI 1.076-2.379, p=0.02), level of education in primary school (OR 1.68, 95% CI 1.203 - 2.362, p=0.002), junior high school (OR 1.59, 95% CI 1.112 - 2.296, p= 0.011), high school (OR 2.44, 95% CI 1.202 - 4.955, p=0.011), familyีs monthly income < 10,000 baths per month (OR 1.73, 95%CI 1.220 - 2.468, p=0.002), poor quality ANC (OR 2.59, 95%CI 1.860-3.610, p<0.001), motherีs height £ 150 centimeter (OR 2.62, 95%CI 1.604-4.288, p<0.001), normal weight before pregnancy £ 55 kilograms (OR 1.81, 95%CI 1.237-2.661, p=0.002), maternal weight gain during pregnancy < 10 kilograms (OR 2.77, 95%CI 1.981-3.864, p <0.001), if maternal weight gain < 7 kilograms and <5 kilograms Odd ratio were increased to 4.30 and 9.86 respectively, complications during pregnancy (OR 4.70, 95%CI 2.671-8.283, p <0.001), uterine fundal height £ 30 cemtimeters (OR 11.21, 95% CI 7.587-16.556, p < 0.001), and abnormality or complication of infants (OR 4.63, 95%CI 3.027-7.097, p <0.001).